The reliability of a peak VO2 test protocol for running in the water with wet vest - Stallman, R. K.; Naess, G.; Vik, B.; Kjendlie, P. L. (Biomechanics and Medicine in Swimming X, 2006)
This study employed a T,-T2 format to examine the reliability of a peak VO2 test protocol for running in the water with the wet vest. Sixteen subjects 20-31 yrs of age participated. Classic Douglas bag respirometry was used. After a 10 minute warm up (HR 110-115 BPM), five 5 minute sub-maximal work loads were performed with a one minute rest interval. Thereafter, a final effort of 3.0-3.5 min. to exhaustion was performed. Work load was controlled by continuous HR monitoring. Blood samples were taken for blood La analysis before and after every work effort. Pearson Product Moment correlations for T1 to T2 were r = 0.99, 0.97 and 0.96 for peak VO2 (l/min), peak VO2 (ml/kg/min) and HR (BPM), respectively. The differences between T1 and T2 were not significantly different at the 0.001 level of confidence.